Coding in Preschool Science and Mathematics Teaching: Analysis of Scratch Projects of Undergraduate Students - Didem KARAKAYA CIRIT (International Journal of Contemporary Educational Research, 2022)
This paper analyzed Scratch projects developed by undergraduate students. The sample consisted of 22 child development students (18 women and four men) in the 2018-2019 academic year. The study adopted an action research design within the scope of a course titled “Teaching Science and Mathematics in Preschool Education.” The research was conducted within 14 weeks. In the first four weeks, we provided participants with training on why and how to use Scratch in science and mathematics teaching. In the following ten weeks, participants designed Scratch projects every week based on age groups, topics, and learning outcomes of their choice. Participants evaluated their projects themselves and also received feedback from peers and academics. Each participant designed ten Scratch projects (five for math and five for science). The data consisted of 220 Scratch projects and design logs. The data were analyzed using content analysis. In the first weeks, participants knew little about the content of Scratch and used one or two characters and mostly control and looks blocks. In the following weeks, they learned more about Scratch and used different Blocks.